IMF Policies and Nigeria’s Relationship : Lending Preconditions From 2019 To 2024. - Sulaiman T.H; Ajiteru,S.A.R; Abalaka, J.N (Green Economics: International Journal of Islamic and Economic Education, 2025)
Nigeria's economy has been severely stagnant since the 1980s. Afrocentric literature charts the nation's history, whereas Eurocentric literature identifies the Nigerian civil war and the corrupt practices of its leaders as the primary cause economic hardships to her historical colonial dominance and economic exploitation activities. However, none of the aforementioned reasons provide stronger support for being the cause of the nation's economic dysfunction, particularly when contrasted with IMF measures implemented there. The IMF's policies on Nigeria's Structural Adjustment Program (SAP) and its Loan Conditionality are partially shown in this article to be "the crux impediment facing the country." As a result, the paper makes the case that, among other mismanagement policies, General Ibrahim Babangida's acceptance of IMF loans contributed to the nation's economic problems and backwardness. Using primary and secondary sources, the study makes the argument that its riches would be restored by a more inclusive economic system free of the current extractive economic practices.